Environmental Communication Activities in Clean Up and Education Program by Trash Hero Jogja Community - Sihaloho, Yeremia; Arifin, Pupung (Fakultas Ilmu Komunikasi UKWMS, 2025)
ABSTRACT The city of Yogyakarta has been experiencing a waste emergency since 2023 because the Piyungan landfill has exceeded its waste capacity and was temporarily closed. As a result of the closure, there is faithfully a lot of waste that fails to be processed. The Trash Hero Jogja community is one of the communities that helped the government's efforts in responding to the waste emergency that occurred in Yogyakarta. More than 928,445 kg of waste has been handled since 2022. This research aims to find out the environmental communication model in the clean up and education program by the Trash Hero Jogja community. This research uses a case study method with data collection techniques in the form of observation, documentation study and in-depth interviews. This study concluded that the convergence communication model plays an important role in achieving understanding between the Trash Hero Jogja community and the community and stakeholders regarding environmental issues. The researcher also found that this community does not evaluate the community and stakeholders regarding clean-up and education programs. ABSTRAK Kota Yogyakarta telah mengalami darurat sampah sejak tahun 2023 karena tempat pembuangan akhir Piyungan telah melebihi kapasitas sampah dan ditutup sementara. Imbas penutupan tersebut, setia hari ada banyak sampah yang gagal untuk diolah. Komunitas Trash Hero Jogja merupakan salah satu komunitas yang membantu upaya pemerintah dalam merespons darurat sampah yang terjadi di Yogyakarta. Lebih dari 928,445 kg sampah yang telah ditangani sejak tahun 2022. Penelitian ini bertujuan untuk mengetahui model komunikasi lingkungan dalam program clean up dan edukasi oleh komunitas Trash Hero Jogja. Penelitian ini menggunakan metode studi kasus dengan teknik pengumpulan data berupa observasi, studi dokumentasi dan wawancara mendalam. Penelitian ini menyimpulkan bahwa model komunikasi konvergensi memainkan peran penting dalam mencapai kesepahaman antara komunitas Trash Hero Jogja dengan masyarakat dan pemangku kepentingan mengenai isu lingkungan. Peneliti juga menemukan bahwa komunitas ini tidak melakukan evaluasi terhadap masyarakat dan pemangku kepentingan mengenai program clean up dan edukasi.